Letter from Julia Morgan to Cousin Lucy and Cousin Pierre Le Brun, May 7, 1899 - Julia Morgan::::::author::: (1899)
On May 7th, 1899 Julia Morgan wrote to her cousins Lucy and Pierre Le Brun. She thanks them for a catalogue they sent and tells them of the interest it garnered. She writes of her preparations for examinations and a boil she got in her ear. She describes the preparations for the Exposition Universelle occurring along the river Seine and of the operas they recently attended. She shares her experience at Notre Dame Cathedral for Easter vespers and her developing plans for vacation with Avery. She notes that one of the California girls studying in Paris died. She ends the letter with pleasantries.